STUDY OF POTENTIAL DRUG INTERACTIONS IN MIGRAINE PATIENTS WITH COMORBIDITIES AT TANJUNGPURA UNIVERSITY HOSPITAL PONTIANAK - Yuandini, Neisya; Susanti, Ressi; Kusharyanti, Indri (Universitas Tanjungpura, 2025)
Migraine patients have the potential of drug interactions due to polypharmacy-related comorbidities. Drug interactions can trigger therapeutic failure because they can affect drug effectiveness. This study aims to assess interacting drugs as well as the type and severity of drug interactions in migraine patients at Tanjungpura University Hospital Pontianak. This study was a non-experimental study with a descriptive cross-sectional design. Data were collected retrospectively through 25 medical records of migraine patients in 2022-2023 with a purposive sampling technique. The results show that drugs with potential interactions in migraine patients with comorbidities are ergotamine+caffeine, ibuprofen, metampirone+diazepam, diclofenac sodium, paracetamol, valproic acid, propranolol, and amitriptyline. The types of potential drug interactions found are pharmacodynamic (39.62%), pharmacokinetic (30.18%), and unknown (30.18%), with moderate (62.26%), minor (30.18%), and major (7.54%) severity. This study conclude that ergotamine+caffeine is the drug with the most potential interactions. The most potential interactions are pharmacodynamic interactions and moderate interactions.